Parental Opinion toward Problem Behaviors among Preschool Children in Pattani Province, Thailand: A Cross–Sectional Study - Mayuening Eso; Rhysa McNeil; Halimah Awang (Advances in Public Health)
The educational performance of children in the three southern border provinces is the lowest in Thailand. This area has been continuously facing unrest, and the COVID-19 crisis has resulted in increased social inequality in schools. The purposes of this study were to determine the problem behaviors exhibited by preschool children in an early childhood center and investigate the association between those behaviors and their related factors. A total of 140 children, aged 2–4, from three early childhood centers were sampled. The dependent variable of the study was a problem behavior with a binary value. The determinants were the children’s demographic information; their parent’s demographic information; and their behaviors of using a smartphone, watching TV, and spending quality time with the children and parent. The association between outcome and determinants was investigated using multiple logistic regression. The prevalence of problem behavior among preschool children was 44.3%. Three factors were associated with problem behavior: family type, allowing children to use smartphones, and children watching television on average per day. Compared to the overall prevalence, the children in the extended family had a high prevalence of problem behavior (62.5%). The children who were disallowed from using a smartphone demonstrated a high prevalence of problem behavior (79.1%). In contrast, children who watched television for more than 3 hr per day exhibited lower problem behavior (21.6%). The results of this study are beneficial to teachers and parents in monitoring their children’s development. Prompt intervention upon early detection of problems in children fosters their development and facilitates learning to their full potential.